Lokasi Pembangunan Pembangkit Listrik Tenaga Bayu Menggunakan Metode SIG di Provinsi Gorontalo - GHINIA ANASTASIA MUHTAR (Jurnal Azimut, 2019)
An analytical study is conducted on the potential of wind energy in Gorontalo Province for wind plant development considering that many developing countries had done so. Wind speed in each region in Gorontalo Province was statistically analyzed, identified potential areas, and calibrated wind speed to wind power density. Based on KTA value it results 3 category, namely good (20 watt/meter2 - 23 watt/meter2), enough (12 watt/meter2 - 20 watt/meter2) and poor (7watt/meter2 - 12 watt/meter2). Then only the KTA value in the good and enough category are used as the land suitability standard. Multi criteria used here is buffering technique by giving a distance between land that can be built by wind plant and land that cannot be built by wind plant. There are 6 layers used in multi criteria, 4 layers use buffering techniques (land use and land cover, land sanctuary, road and public transport terminal), while the other 2 are reclass (lereng and KTA). GIS is used for mapping the distribution of land suitability with the overlay and separation method. The results, total area of land suitability start from 1 hectar until 3.413 hectars. There are ten sub-disctricts which have land suitability more than 1.200 hectars, namely Kwandang, Dulupi, Anggrek, Bongomeme, Tibawa, Pulubala, Wonosari, Sumalata, Boliyohuto and Paguyaman (largest to smallest).